PROBLEMATICS OF RELEASE OF PRISONERS IN INDONESIA IN THE COVID-19 PANDEMIC - Erdianti, Ratri Novita; Al-Fatih, Sholahuddin (Kertha Semaya : Journal Ilmu Hukum; Vol 9 No 10 (2021)DO - 10.24843/KS.2021.v09.i10.p10, 2021)
This study aimed to find the effect of realses of prisoner during Covid-19 pandmeic in Indonesia. The outbreak of the Covid 19 virus has become a major disaster for countries in the world, including Indonesia. One of the influential lives is living in a correctional facility. It becomes a big problem when the state is trying to find a solution to contain the virus but still must provide guidance in the correctional facilities for prisoners. With the concern that there will be a high chance of transmission in prisons, given the overcapacity conditions in prisons, thus the Minister of Law and Human Rights issued a policy through Regulation of the Minister of Law and Human Rights No. 10 of 2020, which contains the release of child prisoners and prisoners. This research uses normative juridical method to explain the effect of release of rpsioner during Covid-19 pandemic in Indonesia. This study found that along with the release of these prisoners, it turns out that the increasing number of crimes that occurred during the Covid 19 pandemic. For reasons of economic pressure, in this case, crime in several areas in Indonesia is very disturbing to the community and mostly committed by ex-convicts who have just been released from Correctional Institutions. It becomes a problem for the country in this case to tackle the spread of the coronavirus but at the same time seek countermeasures against the rampant crime during the Covid 19 pandemic.